Cytokine Response to Acute Endurance Exercise: Regular Treadmill Versus Lower Body Positive Pressure Treadmill - Muhammed Salih Kırışka; Nilsel Okudan; Muaz Belviranlı (Genel Tıp Dergisi)
Background/Aims: This study aimed to investigate the cytokine response to acute endurance exercise performed in the LBPPT and to compare it with the regular treadmill. METHODS: Eleven healthy physically active men aged between 18-22 years participated in the study. All subjects performed 45 minutes of running exercise at 70% VO2max on the regular treadmill and LBPPT in random order, one week apart. Blood samples were collected at pre-exercise, immediately post-exercise, 30 min post-exercise, and 2 h post-exercise to analyze serum high sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-alpha (TNF-α), and interleukin-8 (IL-8) levels. RESULTS: On the regular treadmill, hs-CRP levels were higher immediately, 30 min, and 2 h post-exercise than pre-exercise. In addition, it was lower 2 h post-exercise compared with immediately, and 30 min post-exercise. No significant differences in LBPPT for hs-CRP were observed for any time point. hs-CRP concentration immediately and 30 min post-exercise was lower in the LBPPT than in the regular treadmill. TNF-α and IL-8 levels were unchanged in response to exercise performed neither on the regular treadmill nor on the LBPPT. CONCLUSIONS: Acute endurance exercise may not be sufficient to induce a significant systemic inflammatory response in physically active men.